Envelop of reachable asteroids by M-ARGO CubeSat. Issue 12 (15th June 2021) - Topputo, Francesco; Wang, Yang; Giordano, Carmine; Franzese, Vittorio; Goldberg, Hannah; Perez-Lissi, Franco; Walker, Roger
Abstract: The Miniaturised Asteroid Remote Geophysical Observer (M-ARGO) is planned to be the first standalone deep-space CubeSat mission to rendezvous with and characterise a near-Earth asteroid. To this aim, it is essential to assess the attainable set of target asteroids. This work presents the initial results of the mission analysis and design of M-ARGO. In particular, the original procedure developed to extract the reachable near-Earth asteroids and the subsequent down-selection process are shown. Hundreds of both time- and fuel-optimal low-thrust trajectory optimisation problems have been solved with an indirect approach, targeting asteroids pre-filtered from the Minor Planet Center Database. The method implements a realistic thruster model, featuring variable input power, thrust, and specific impulse, together with an accurate switching detection technique and analytic derivatives. The analysis shows that approximately 150 minor bodies are found potentially reachable by M-ARGO when departing from the Sun–Earth Lagrange point L 2 within a 3-year transfer duration. A manual inspection of the transfer features led to a subset of 41 targets seeming more promising according to mission technological requirements and constraints. Initial results indicate mission feasibility for M-ARGO, which has the potential to enable a completely new class of low-cost deep-space exploration missions.